Nitrogen Addition Exacerbates the Negative Effects of Low Temperature Stress on Carbon and Nitrogen Metabolism in Moss - Liu, Bin-Yang; Lei, Chun-Yi; Liu, Wei-Qiu (Frontiers in Plant Science, 2017)
1 Introduction The overall trend of global climate change is warming; however, the accelerated melting and disappearance of Arctic Sea-Ice has also led to increasing local occurrences of abnormally low temperatures (Mori et al., 2014; Overland et al., 2015). Low temperature stress (LTS) damages plants by inducing oxidative stress, hindering photosynthesis, and indirectly inducing osmotic stress (Nuccio et al., 1999; Allen and Ort, 2001; Beck et al., 2007). Increasing nitrogen (N) deposition is another environmental problem which attracts global attention (Stevens et al., 2004; Galloway et al., 2008; Liu et al., 2013). Excess N deposition leads to nutritional imbalance, cell membrane destruction and oxidative stress in plants (Pearce and Van der Wal, 2002; Koranda et al., 2007). N in wet deposition mainly occurs in the forms of NO3- and NH4+, but they have different effects on plants. On the one hand, as H+ is generated during NH4+ assimilation, whereas OH- is generated during NO3- assimilation, NH4+ is more apt to decrease tissue pH and disrupt membrane function (Pearce et al., 2003, Paulissen et al., 2004). On the other hand, NH4+ is more readily available than NO3- for utilization by plants as less energy is needed during its assimilation (Flaig and Mohr, 1992). Moreover, excess N deposition can reduce the resistance of plants to LTS (Fenn et al., 1998); this phenomenon merits attention, although the underlying mechanisms have seldom been investigated. The resilience of plants to stress, namely the ability of plants to recover growth after removal of stress factors, is vital for their survival in natural environments. This phenomenon, referred to as the “compensation effect” (Belsky, 1986), exists widely in various plants, and has been studied extensively in agriculture and stockbreeding. However, the effects of N deposition on compensation effects after LTS in plants is poorly understood, despite the importance of precise evaluation of the effects of global change on plants and ecosystems. Mosses, a group of primitive land plants with small stature that mainly acquire their nutrients from air, are relatively sensitive to environmental change, and, therefore, generally more vulnerable to global changes than vascular plants (Pearce and van